Chemically-assisted DNA transfection methods: An overview - Bekić Sofija S.; Jovanović-Šanta Suzana S. (Journal of the Serbian Chemical Society, 2023)
Non-viral chemical-based methods for in vitro cell transfection are commonly used to incorporate foreign gene of interest into mammalian cells due to numerous benefits – high efficiency, low cost and simple methodology. These powerful transfection methods generally do not possess safety risks as virus-based, and cell toxicity is significantly reduced. To obtain transfectants, host cells are usually treated with biocompatible DNA carriers such as calcium phosphate, cationic lipids, DEAE-dextran, polyethylenimine or dendrimers, classifying these methods based on chemical reagents used. All these different approaches are based on the similar principle, namely formation of encapsulated amphiphilic complexes between DNA and various particles, following cell uptake, most likely mediated by endocytosis. Depending on the aim and design of experiment, the choice of appropriate method is made. This review article outlines strategies of the most widely used chemical transfection techniques, pointing out advantages and limitations of different DNA carriers, also findings of researchers as how to optimize and enhance efficiency of gene delivery procedure. With methodology constantly being improved, transfection methods described here find their main, biomedical application in gene therapy, a promising way to introduce functional copy of exogenous gene to genetically defective target cells.